Collider signature of e+e- H+H- in the Scotogenic model - Elmahdy, Nagat A.; Al-Mellah, Asmaa; Akyıldırım, Hakan (International Journal of Computational and Experimental Science and Engineering, 2023)
We investigate the process e+e- H+H- in the framework of the scotogenic model. The process receives different contributions arising from tree-level diagrams mediated by photon exchange, Z boson exchange and from the exchange of new singlet right-handedfermions N 1,2,3. We estimate the size of each contribution and the total cross section of the process after applying alldominant constraints on the parameters of the model. We show that the dominant contribution to the cross section originate from the newsinglet right-handedfermions N 1,2,3. Additionally, weshow the dependency of the cross section on the centreof mass energy for set of benchmark points of the parameter space of the model respecting the strong obtained bounds. These predictions canbe tested in future e+e- colliders and hence can test the validity of the model or setting further strong constraints on the model.